Pengaruh Tingkat Pendapatan, Literasi Keuangan dan Toleransi Risiko Terhadap Pembelian Saham - Jhon Rinendy; Grace Orlyn Sitompul; Francis Hutabarat (Jurnal Akuntansi, 2023)
Society is required to manage its resources for future welfare. One solution is to invest in stocks. This research aims to determine income level, financial literacy, and risk tolerance influence stock purchasing decisions. The study was conducted using a quantitative approach, examining a population of professional workers from several regions in Indonesia with income available for investment and recognizing stocks as one of the investment instrument choices. Data was collected using the purposive random sampling method, with 239 valid data. The research findings indicate that a person's decision to invest in stocks is influenced by their income level, financial literacy, and risk tolerance.Keywords: Level Of Income, Financial Literacy, Risk Tolerance, Stock Purchase.